Online medium of International Linkage; Entrepreneurs and Youngsters - Mohamad Saad, Mohamad Zaki; Kamarudin, Shafinah; Kamilah, Hanisah; Maikol, Nathaniel; Ramlan, Nur Hafizatun (Akademia Baru Publishing, 2024)
Since 2016, the Fourth Industrial Revolution (IR 4.0) has contributed a positive effect on current business and educational developments in Malaysia. Therefore, various organisations are actively engaged in sharing knowledge and information with the public as part of the impact of the establishment. Hence, higher education institutions (IPT) and non-governmental organisations are collaborating to provide early exposure to youth, particularly in the fields of education and business. Due to society's current interest in modernisation, particularly in this digitally driven period, business patterns have accelerated, powering the economies of nations. In response, the online International Linkage Entrepreneur and Youngster (ILEY) program was initiated to share thoughts with the youth and the public. ILEY provided an opportunity for students and fresh graduates to explore the concept of entrepreneurship. The platform focuses on the fundamental online business, as well as the latest technology and applications for online marketing. ILEY was held online, with the involvement of entrepreneurs from Malaysia and Indonesia. This research was conducted using the survey method. The survey form received responses from 110 participants based in Malaysia and Indonesia. The online participants were satisfied with ILEY. During the event, these speakers shared their viewpoints on small business management and strategies for dealing with business issues.